Uma análise do universo ficcional de Doctor Who e de seus arquétipos centrais - Contartesi, Felipe (2017)
Doctor Who, a British series created and produced by the BBC since 1963 has been devoted as one of the oldest and most successful series of fiction for television. The series has set its course and achieved cult status, becoming the success it is today with an extensive amount of episodes and seasons and a large expansion of its narrative universe to other media such as movies, comics, literature, digital and analog games. The expansion of a work brings a series of obstacles, a vast narrative maintained for so long and in so many media, undergoes several changes with the passage of time, the fans can also change or have different expectations. Nevertheless some series like Doctor Who, manage to remain firm and coherent over time. These series can find and construct a solid identity that is interesting and acceptable to its fans, this identity is related to the archetypes of the fictional universe of the series and is what often guides the narrative direction and the migration of this narrative to other media, this study aimed to analyze and punctuate the elements that define this identity of Doctor Who and how this can contribute to the production and study of vast transmedia narratives.